Exploring college students’ resistance to mandatory use of sports apps: a psychological reactance theory perspective - Guo, Jian (Frontiers in Psychology, 2024)
Introduction To improve the physical fitness of college students, numerous Chinese universities have mandated students to use sports apps for running on campus. However, this has led to widespread resistance among students. Methods To gain a deep understanding of the potential reasons for student resistance, we have developed a conceptual model based on psychological reactance theory. Specifically, we conducted a questionnaire survey involving 449 Chinese college students, using partial least squares structural equation modeling to test and analyze the research model and its related hypotheses. Results Our results reveal that: (1) Psychological reactance poses a potential reason for students’ resistance to mandatory use of sports apps, and it has a significant negative impact on students’ attitudes and behavioral intentions. (2) Students’ perceived threat to freedom and reactance proneness are two important antecedents of psychological reactance, which can account for 51% (R2 = 0.51) of the variance in psychological reactance. Furthermore, the results indicate that students’ reactance proneness has a positive impact on perceived threats to freedom. (3) The mandatory use of sports apps leads students to have two different conditions: mandated-acceptance and mandated-rejection, both of which have a positive impact on the antecedents of psychological reactance. Discussion These findings provide insights into the psychological processes underlying students’ resistance to mandatory use of sports apps, facilitating the application of sports apps in intervention measures that improve health and fitness. Furthermore, this study is the first to apply psychological reactance theory to mandatory exercise behavior, contributing to the reactance literature.